Recession and child labor: A theoretical analysis - Sahana Roy Chowdhury (Indian Council for Research on International Economic Relations (ICRIER), 2013)
Child labor (CL) has been a major concern for the developing world, especially for India with its goal towards 'inclusive growth'. However, impact (or vulnerabilities) of major domestic or external spillovers (policy related or recessionary shocks) on child labor market, in contrary to other labor markets, remain unexplored so far. This paper provides a theoretical model of the impact of recession (income shock) on household's child labor (CL) decision. Parental altruism is endogenized; as their choice of substituting child labor income by their own is endogenous. Interestingly, income shocks have ambiguous effect on CL in general, but a clear positive impact on regions with high cost of living. When wages are in inflexible such shocks, depending upon its extent, might be CL inducing as well as poverty enhancing, as in that case there may be dearth of demand for parents' labor supply that support their CL or NCL decisions. It infers that any in-kind transfer or policies such as mid-day meal that essentially reduces cost of living, is always CL reducing.
Keywords: J13; J29; D10; 330; child labor; adult labor choice; poverty line; recession; Kinderarbeit; Konjunkturelle Arbeitslosigkeit; Eltern; Grundbedürfnisse; Haushaltseinkommen; Theorie